Person Job Fit On Employee Performance : The Mediating Role of Job Satisfaction At PT Pegadaian Surabaya - Riswanda Fatchurrozy; Agus Frianto (International Journal of Social, Economic, and Business, 2024)
This study aims to test and analyze the influence of person job fit on employee performance with job satisfaction as a mediating variable. This study uses a quantitative approach involving 48 employees at PT Pegadaian Cabang Pembantu Dinoyotangsi Surabaya. The sampling technique uses a saturated sample of 49 respondents using a non-probability side technique with a saturated sample type. The statistical analysis used in this study is SEM PLS with the help of SmartPLS 3.2.9 software. The findings of this study indicate that person job fit has a significant effect on employee performance. Person job fit has a significant positive effect on Job satisfaction. Job satisfaction has a significant positive effect on Employee performance. Job satisfaction in this study is able to mediate the influence of person job fit and employee performance.